2007
DOI: 10.1242/jcs.001362
|View full text |Cite
|
Sign up to set email alerts
|

Targeted alterations in iron homeostasis underlie plant defense responses

Abstract: Iron (Fe) is a ubiquitous redox-active element essential for most life. The formation of localized cell wall appositions, the oxidative burst and the production of pathogenesis-related proteins are hallmarks of plant defense responses. Here, we report that iron is a central mediator linking these three phenomena. We show that in response to pathogen attack, reactive Fe3+, but not Fe2+, is deposited at cell wall appositions where it accumulates and mediates the oxidative burst. We provide evidence that the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 59 publications
4
126
1
1
Order By: Relevance
“…To test whether ALG3 is important for the induction of ROS in plant cells, ROS production was assayed with 3,39-diaminobenzidine (DAB) staining in barley leaves inoculated with the wild-type and Dalg3 strains as described previously (Liu et al, 2007). Whereas ROS was barely detectable in barley epidermal cells penetrated by the wild-type P131 and complemented strain cALG3, strong induction of ROS was observed in cells infected by the Dalg3 mutant ( Figures 5A and 5B).…”
Section: Alg3 Is Required For Suppressing the Production Of Ros In Plmentioning
confidence: 97%
“…To test whether ALG3 is important for the induction of ROS in plant cells, ROS production was assayed with 3,39-diaminobenzidine (DAB) staining in barley leaves inoculated with the wild-type and Dalg3 strains as described previously (Liu et al, 2007). Whereas ROS was barely detectable in barley epidermal cells penetrated by the wild-type P131 and complemented strain cALG3, strong induction of ROS was observed in cells infected by the Dalg3 mutant ( Figures 5A and 5B).…”
Section: Alg3 Is Required For Suppressing the Production Of Ros In Plmentioning
confidence: 97%
“…This leads to an increase in HR generation and cell death (Becana and Klucas, 1992;Moran et al, 1994;Liu et al, 2007). Thus, it can be hypothesised that the regulation of catalytic activities of transition metals could play a crucial role in plant ROS-mediated regulatory reactions.…”
Section: Possible Mechanisms Of K + -Channel Activation By Hrsmentioning
confidence: 99%
“…This indicates a role in signalling for PCD. Recently, Liu et al (2007) showed that the combined activation of SIPK, Ntf4 and WIPK induced an HR-like PCD.…”
Section: +mentioning
confidence: 99%